THE ROLE OF TRUST IN MEDIATING THE INFLUENCE OF PERCEIVED EASE OF USE AND PERCEIVED USEFULNESS ON CONTINUANCE INTENTION OF THE KAPAJUMA APPLICATION IN DENPASAR CITY - Ni Komang Risa Pebriyanthi; Ni Nyoman Kerti Yasa (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
This study aims to examine and explain the effects of perceived ease of use, perceived usefulness, and trust on the continuance intention the Kapajuma Application in Denpasar City. The background of this study is motivated by the fact that initial success in attracting early users has not been accompanied by success in sustaining continued usage. This research employs a quantitative approach with a causal–associative design, using a survey method through the distribution of questionnaires to 100 Kapajuma application users, selected using purposive sampling, quota sampling, and snowball sampling techniques. Respondent characteristics obtained from the questionnaires were analyzed descriptively using IBM SPSS Statistics 24. The questionnaire data were then analyzed using SmartPLS 3.0 with the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The results indicate that perceived ease of use, perceived usefulness, and trust have positive and significant effects on continuance intention. In addition, perceived ease of use and perceived usefulness also have positive and significant effects on trust. Furthermore, the findings reveal that trust mediates the effects of perceived ease of use and perceived usefulness on continuance intention